GeNepher data- and biobank for patients with (suspected) genetic kidney disease: Rationale, design and status update - Laura R. Claus; Iris Lekkerkerker; Bert van der Zwaag; Tri Q. Nguyen; Nine V.A.M. Knoers; Martin H. de Borst; Maarten B. Rookmaker; Marc R. Lilien; Albertien M. van Eerde (Rare)
Background: Clinical research on monogenic kidney disease (MKD) is thriving and the need for large cohorts, prospective data collection and biobanking is increasing. We aim to create a sustainable large MKD biobank with a vast amount of uniformly collected high-quality data that is readily available for future research, with an infrastructure that allows for recontacting participants. Methods: The GeNepher data- and biobank is an ongoing data- and sample collection that includes patients and family members with known and/or suspected MKD. With a tiered approach participants can give broad consent for including their 1) available medical data (including genetic testing results), 2) inclusion of massively parallel sequencing data for add-on analysis, and 3) additional biobank sampling (e.g. urine for tubuloids, skin biopsy for fibroblasts). Recontacting is possible for additional data collection, novel research opportunities and return of relevant findings. Discussion: The GeNepher data- and biobank collects prospective and retrospective data from kidney disease patients and their relatives. The broad consent allows for research that extends beyond one specific research question. Herewith, this biobank aims to 1) increase the scientific knowledge based on disease mechanisms including (novel) monogenic causes, 2) study modifiers, 3) improve care, including reproduction related research questions. Furthermore, it facilitates recontacting for opportunities in treatment development or when diagnose specific trials are started or specific treatment is approved. Conclusion: The GeNepher biobank is designed to support a wide range of research projects by providing access to a diverse population of patients with (suspected) MKD and has the potential to make a significant contribution to the field of rare kidney disease research.